2003
DOI: 10.1111/j.1151-2916.2003.tb03619.x
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force and Ultrasonic Force Microscopic Investigation of Laser‐Treated Ceramic Head Sliders

Abstract: The surface of laser‐treated ceramic hard disk drive head sliders has been imaged with the atomic force microscope (AFM) and ultrasonic force microscope (UFM). The surface topography image from the AFM is compared with the elasticity image generated by the UFM on the same region. Images of the surface structure changes along with microcracking in the laser‐treated regions are presented. The possible reasons for the development of microcracking and the enhanced contrast that the UFM provides of the microcracks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…But bear in mind that the above discussions are presented to review all the known complications, whereas actual experimental results will often be sensitive primarily to far fewer (and controllable) details. Accordingly, a wide range of UFM measurements has been reported on polymers (16)(17)(18), metals (19,20), semiconductors (21-23), ceramics (24)(25)(26)(27), and a variety of nanomaterials (1,(28)(29)(30). Quantitatively, these studies are generally based on analyzing individual UFM spectra (especially the JOA i and/or the hysteresis area) or differential UFM measurements (essentially comparing JOA i for different setpoint forces).…”
Section: Ultrasonic Amplitude (å) Ufm Deflection (å)mentioning
confidence: 99%
“…But bear in mind that the above discussions are presented to review all the known complications, whereas actual experimental results will often be sensitive primarily to far fewer (and controllable) details. Accordingly, a wide range of UFM measurements has been reported on polymers (16)(17)(18), metals (19,20), semiconductors (21-23), ceramics (24)(25)(26)(27), and a variety of nanomaterials (1,(28)(29)(30). Quantitatively, these studies are generally based on analyzing individual UFM spectra (especially the JOA i and/or the hysteresis area) or differential UFM measurements (essentially comparing JOA i for different setpoint forces).…”
Section: Ultrasonic Amplitude (å) Ufm Deflection (å)mentioning
confidence: 99%
“…It has been found that in many materials, even if contrast is poor in AFM images, the elastic property variations imaged in UFM enhances the contrast [14], [15]. This particularly becomes useful when the surface topography variations imaged in AFM is extremely low.…”
Section: Introductionmentioning
confidence: 95%
“…The approach used in the present investigation has been described in detail in a previous study 26 . In brief, a piezo-electric transducer was attached to one face of the sample, and excited with a low amplitude continuous wave radio frequency signal in the range of 0.5 to 1.0 MHz.…”
Section: Afm-ufmmentioning
confidence: 99%